2010
DOI: 10.1373/clinchem.2010.151233
|View full text |Cite
|
Sign up to set email alerts
|

Automated Extraction of DNA and RNA from a Single Formalin-Fixed Paraffin-Embedded Tissue Section for Analysis of Both Single-Nucleotide Polymorphisms and mRNA Expression

Abstract: BACKGROUND:There is an increasing need for the identification of both DNA and RNA biomarkers from pathodiagnostic formalin-fixed paraffin-embedded (FFPE) tissue samples for the exploration of individualized therapy strategies in cancer. We investigated a fully automated, xylene-free nucleic acid extraction method for the simultaneous analysis of RNA and DNA biomarkers related to breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 16 publications
1
53
0
1
Order By: Relevance
“…Total RNA was extracted from one 5-or 10-mm whole FFPE tissue section with a silica bead-based, fully automated isolation method (Tissue Preparation System, VERSANT Tissue Preparation Reagents, Siemens Healthcare Diagnostics) as described in Supplementary Appendix (13). All samples were analyzed with quantitative one-step reverse transcriptase PCR (qRT-PCR) on an ABI PRISM 7900HT (Applied Biosystems) using SuperScript III PLATINUM One-Step Quantitative RT-PCR System with ROX (Invitrogen).…”
Section: Rna Extraction and Gene Expression Analysis With Quantitativmentioning
confidence: 99%
“…Total RNA was extracted from one 5-or 10-mm whole FFPE tissue section with a silica bead-based, fully automated isolation method (Tissue Preparation System, VERSANT Tissue Preparation Reagents, Siemens Healthcare Diagnostics) as described in Supplementary Appendix (13). All samples were analyzed with quantitative one-step reverse transcriptase PCR (qRT-PCR) on an ABI PRISM 7900HT (Applied Biosystems) using SuperScript III PLATINUM One-Step Quantitative RT-PCR System with ROX (Invitrogen).…”
Section: Rna Extraction and Gene Expression Analysis With Quantitativmentioning
confidence: 99%
“…Reactions were carried out on an ABI Prism 7900 Sequence Detector (ABI) and in duplicate. Seven potential reference genes were analyzed: ACTR3, CHCHD1, NDFIP1, SPCS2, and TMEM85 were selected on the basis of our previous in vitro results (27); RPL37A and TFRC have previously been described (35,36). The geNORM application available in RealTime Statminer (Intergromics) was used on the training set of 58 HNSCC samples, and 3 optimal reference genes (RPL37A, ACTR3, and NDFIP1) were selected for normalization.…”
Section: Hypoxia Tracer and Isolation Of Hypoxic Xenograft Tissuementioning
confidence: 99%
“…A study of peripheral blood mononuclear cells (PBMCs) from lung cancer patients identified a signature of 29 genes that distinguished patients from controls (46). Panels of mRNA biomarkers for early detection have also been identified in bladder, breast and renal carcinomas (47)(48)(49). These studies suggest that blood-based mRNA signatures may be potentially useful tools for the early detection of lung cancer.…”
Section: Lung Cancer Biomarkers On the Basis Of Biomoleculesmentioning
confidence: 99%